Numerical study on structural performance of corrugated steel plate shear wall with different yield points steel. (9th December 2022) - Li, Gang; Wei, Xing; Xiao, Lin; Zhou, Linjun
Summary: As a new type of lateral load‐resisting system in SPSW systems, corrugated SPSWs (CSPSWs) have been gradually researched and applied. Corrugated plates offer various advantages over flat plates including higher energy dissipation capacity, ductility, out‐of‐plane stiffness, and improved buckling stability. For seismic control and isolation techniques, low yield point (LYP) steels (LY100, LY160, and LY225) are the reliable and ideal energy‐dissipating materials. The low yield point CSPSWs combine high energy‐consuming materials with high‐performance structures to provide a better solution for ductile and seismic resistance of high‐rise and super tall buildings. Currently, there are no design codes addressing the seismic performance of LYP corrugated steel plate shear walls (CSPSWs). This study investigates cyclic behavior and energy dissipation performance of corrugated steel plate yield point (100, 160, 225, 235, and 345 MPa) of different thickness CSPSWs and determine the plate yield point that provides the optimum performance. Results and findings of this study reveal that compared with the ordinary yield strength corrugated steel plates, the low yield point CSPSWs have a larger safety factor of lateral bearing capacity, a fuller hysteresis curve, a strong energy dissipation coefficient, a larger ductility coefficient and a smaller fluctuation range of strength degradation coefficient, and better strength stability. The initial equivalent stiffness of CSPSWs with different yield strengths is the same.